Preparation method of ceramic dielectric filter

By alternately printing the medium and electrode paste in the porcelain dielectric filter and performing drying lamination treatment, the problems of poor density and insufficient pressure resistance of the porcelain dielectric filter in the prior art are solved, and high conductivity and wide application are achieved sex.

CN119275528APending Publication Date: 2025-01-07GUANGDONG FENGHUA BANGKE ELECTRONIC CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411389651.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing ceramic dielectric filters have poor density when the electrode thickness is high when the capacity is high, which is prone to internal stress and bubbles, affecting the conductivity; thin electrode thickness is poor withstand current, which is not suitable for high voltage and high current products.

Method used

The primary slurry is obtained by directly selecting the ratio of adhesive to ceramic powder and high-speed stirring. After pretreatment, the medium and electrode slurry are alternately printed on the metal bearing plate to form a multi-layer structure and drying and laminating are carried out to improve density and pressure resistance.

Benefits of technology

It improves the conductivity and voltage resistance of the porcelain dielectric filter, expands the scope of application, and can meet the filter needs of high capacity, high voltage and high current.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275528A_ABST
    Figure CN119275528A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ceramic dielectric filter, which comprises the following steps: proportioning and stirring an adhesive and ceramic powder to obtain primary slurry; pre-treating the primary slurry of the first dielectric protection layer to obtain dielectric slurry; pasting a polyester film on the metal bearing plate, and printing a first dielectric protection layer dielectric paste with a preset thickness on the first dielectric protection layer polyester film to obtain a first dielectric protection layer; printing electrode slurry with a preset thickness on the first medium protection layer, and performing drying treatment to obtain an electrode material; printing first dielectric protection layer dielectric paste with a preset thickness on the first dielectric protection layer electrode material to form a second dielectric protection layer and obtain a primary ceramic dielectric filter; and drying and laminating the primary ceramic dielectric filter with the first dielectric protection layer to obtain a finished ceramic dielectric filter product. The conductive performance of the ceramic dielectric filter is improved, and meanwhile the voltage resistance of the ceramic dielectric filter is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of filters, and in particular to a method for preparing a ceramic dielectric filter. Background Art

[0002] Ceramic dielectric filters are a type of filter made using the piezoelectric effect of ceramic materials. They are widely used in various electronic devices, especially in 5G communication technology. Ceramic dielectric filters are used in feedback lines in circuits. Ceramic dielectric filters have both capacitive filtering effects and inductive filtering effects. They also have high Q values, good amplitude-frequency and phase-frequency characteristics, small size, and high signal-to-noise ratio.

[0003] In the relevant technology, the current industry's ceramic filter capacity below 100nF can only achieve a maximum current level of 6A. The main problem is that the dielectric layer is thin under the condition of high ceramic filter capacity. If the electrode thickness of the ceramic filter is higher than the dielectric thickness, there will be gaps on the edge of the electrode and the density is poor. In addition, when the number of electrode layers is high, internal stress will easily be generated during sintering, resulting in internal bubbles and cracks, affecting the conductive performance characteristics of the ceramic filter. However, when the electrode thickness is too thin, it will affect the current resistance of the filter, resulting in a voltage resistance difference of the filter. It is not suitable for high-power and high-voltage products and has a narrow range of applications. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application provides a method for preparing a ceramic filter, which is conducive to improving the conductivity of the ceramic filter and the pressure resistance of the ceramic filter.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a ceramic filter, comprising:

[0006] The binder and the ceramic powder are mixed and stirred to obtain a primary slurry;

[0007] Pre-treating the primary slurry to obtain a medium slurry;

[0008] A polyester film is attached to the metal carrier plate, and the dielectric slurry having a preset thickness is printed on the polyester film to obtain a first dielectric protective layer;

[0009] Printing an electrode slurry with a preset thickness on the first dielectric protection layer, and performing a drying process to obtain an electrode material;

[0010] Printing the dielectric slurry with a preset thickness on the electrode material to form a second dielectric protection layer to obtain a primary ceramic dielectric filter;

[0011] The primary ceramic filter is dried and laminated to obtain a finished ceramic filter.

[0012] The technical solution of the first aspect of the present application has at least one of the following advantages or beneficial effects: the primary slurry for preparing the ceramic dielectric filter is obtained by directly selecting the ratio of the adhesive and the ceramic powder and high-speed stirring, which is more efficient than obtaining the primary slurry by ball milling in the prior art. Afterwards, the primary slurry is pretreated to obtain a dielectric slurry, a polyester film is attached to a metal carrier plate, and then the dielectric slurry of a preset thickness is printed on the polyester film to obtain a first dielectric protective layer; an electrode slurry of a preset thickness is printed on the first dielectric protective layer, and a drying treatment is performed to obtain an electrode material, and a dielectric slurry of a preset thickness is printed on the electrode material to form a second dielectric protective layer to obtain a primary ceramic dielectric filter. By alternately printing the electrode material and the dielectric slurry, the combination of the dielectric and the electrode can be ensured, the density of the ceramic filter can be improved, and the conductivity of the ceramic filter can be improved; the primary ceramic filter is dried and laminated to obtain a finished ceramic filter. By drying and laminating the primary ceramic filter, sintering shrinkage can be prevented, ensuring that the ceramic filter has good electrical properties and mechanical strength, and improving the pressure resistance of the ceramic filter. It can meet specific frequency selection and signal processing requirements, and can be used as a high-capacity, high-voltage, and high-current filter product, which increases the application range of the ceramic filter.

[0013] According to some embodiments of the present application, after the drying and laminating process is performed on the primary ceramic filter, the method further includes:

[0014] Carry out cutting and debonding treatment on the ceramic dielectric filter which has been dried and laminated;

[0015] The ceramic dielectric filter that has undergone drying and lamination treatment is subjected to sintering treatment, end-sealing treatment and end-burning treatment;

[0016] The dried and laminated ceramic filter is electroplated to obtain a finished ceramic filter.

[0017] According to some embodiments of the present application, pre-treating the primary slurry to obtain the medium slurry includes:

[0018] Adding a solvent, a plasticizer, and a dispersant to the primary slurry, stirring and mixing, to obtain a mixed solvent;

[0019] The mixed solvent is placed on an emulsifier for emulsification, or the mixed solvent is placed on a roller mill for a preset number of times to obtain a medium slurry.

[0020] According to some embodiments of the present application, placing the mixed solvent on a roller mill for a preset number of times to obtain a medium slurry comprises:

[0021] The mixed solvent is heated to 60° C.

[0022] The mixed solvent was stirred at a speed of 60 rpm for 20 minutes, and rolled on a roller mill for 1 to 10 times to make the viscosity of the mixed solvent below 40 KCP, thereby obtaining a medium slurry.

[0023] According to some embodiments of the present application, after obtaining the medium slurry, the method further includes:

[0024] The medium slurry is selected, and the medium slurry is subjected to viscosity test, solid content test, fineness test, and vacuum defoaming treatment to ensure that the medium slurry meets the required medium slurry particle size requirement.

[0025] According to some embodiments of the present application, the method for preparing the adhesive includes:

[0026] Polyvinyl butyral, cellulose resin and acrylic resin are selected as raw materials for preparing the adhesive;

[0027] The polyvinyl butyral, cellulose resin and acrylic resin are mixed in a ratio of 6:2:1, added into an organic solvent and the organic solvent is heated to 30° C. to 80° C. so that the raw materials of the adhesive account for 45%-75% of the organic solvent to obtain an adhesive.

[0028] According to some embodiments of the present application, printing an electrode slurry of a preset thickness on the first dielectric protection layer and performing a drying process to obtain an electrode material includes:

[0029] Printing a first layer of electrode slurry with a thickness of 1 μm to 15 μm on the dielectric protection layer, and placing it in a temperature environment of 30° C. to 80° C. to dry for 5 minutes to 25 minutes;

[0030] Printing a second layer of electrode slurry with a thickness of 2 μm to 200 μm on the dried dielectric protective layer, and placing it in an environment of 30° C. to 80° C. to dry for 10 minutes to 50 minutes;

[0031] The dielectric protection layer and the electrode paste are alternately printed on the dried second electrode paste layer until the thickness of the electrode paste reaches a preset thickness, and each printed dielectric protection layer or electrode paste layer is dried to obtain an electrode material.

[0032] According to some embodiments of the present application, the drying and laminating process is performed on the primary ceramic filter to obtain a finished ceramic filter, including:

[0033] The primary ceramic filter is placed in a temperature environment of 30° C. to 50° C. for drying for 1 to 24 hours;

[0034] The dried primary ceramic filter is placed under an air pressure of 20 MPa to 100 MPa for lamination for 5 to 60 minutes.

[0035] According to some embodiments of the present application, the organic solvent includes an alcohol solvent and an ester solvent.

[0036] According to some embodiments of the present application, the ceramic powder is a mixed material of barium titanate series, strontium titanate series, and zirconium titanium series.

[0037] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings are used to provide a further understanding of the technical solution of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the technical solution of the present invention and do not constitute a limitation on the technical solution of the present invention.

[0039] The present invention is further described below in conjunction with the accompanying drawings and embodiments;

[0040] Figure 1 It is a flow chart of a method for preparing a ceramic dielectric filter provided in an embodiment of the present application;

[0041] Figure 2 is a flow chart of another method for preparing a ceramic filter provided in an embodiment of the present application;

[0042] Figure 3 It is a flow chart of a method for pretreating a primary slurry to obtain a medium slurry provided in an embodiment of the present application;

[0043] Figure 4 It is a flow chart of a method provided in an embodiment of the present application for placing a mixed solvent on a roller mill and rolling it for a preset number of times to obtain a medium slurry;

[0044] Figure 5 is a flow chart of a method for preparing an adhesive provided in an embodiment of the present application;

[0045] Figure 6 is a flow chart of a method for obtaining an electrode material provided in an embodiment of the present application;

[0046] Figure 7 It is a flow chart of a method for drying and laminating a primary ceramic filter to obtain a finished ceramic filter provided in an embodiment of the present application. DETAILED DESCRIPTION

[0047] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.

[0048] In the description of the present invention, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, "any one" means one or more, "at least one of the following" and similar expressions refer to any combination of these items, including any combination of single or plural items. If there is a description of the first and the second, it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0049] It should be noted that the terms such as setting, installing, and connecting in the embodiments of the present invention should be understood in a broad sense, and those skilled in the art can reasonably determine the specific meanings of the above terms in the embodiments of the present invention in combination with the specific content of the technical solution. For example, the term "connection" can be a mechanical connection, an electrical connection, or mutual communication; it can be directly connected or indirectly connected through an intermediate medium.

[0050] It should be noted that the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0051] Please refer to the accompanying drawings to further illustrate a method for preparing a ceramic filter provided in an embodiment of the present application.

[0052] Reference Figure 1 As shown, Figure 1 is a flow chart of a method for preparing a ceramic filter provided in an embodiment of the present application. The method for preparing the ceramic filter includes but is not limited to steps S100 to S600. Specifically,

[0053] Step S100: mixing and stirring the binder and ceramic powder to obtain a primary slurry;

[0054] Step S200: pre-treating the primary slurry to obtain a medium slurry;

[0055] Step S300: attaching a polyester film to the metal carrier plate, and printing a dielectric slurry with a preset thickness on the polyester film to obtain a first dielectric protective layer;

[0056] Step S400: printing an electrode slurry with a preset thickness on the dielectric protection layer, and performing drying treatment to obtain an electrode material;

[0057] Step S500: printing a dielectric slurry of a preset thickness on the electrode material to form a second dielectric protection layer to obtain a primary ceramic filter;

[0058] Step S600: drying and laminating the primary ceramic filter to obtain a finished ceramic filter.

[0059] In some embodiments of the present application, the preparation method of the ceramic dielectric filter includes: obtaining a primary slurry for preparing the ceramic dielectric filter by directly selecting a ratio of an adhesive and a ceramic powder and high-speed stirring, which is more efficient than obtaining the primary slurry by ball milling, pre-treating the primary slurry to obtain a dielectric slurry, attaching a polyester film to a metal carrier plate, and then printing a dielectric slurry of a preset thickness on the polyester film to obtain a first dielectric protective layer; printing an electrode slurry of a preset thickness on the first dielectric protective layer, and drying it to obtain an electrode material, printing a dielectric slurry of a preset thickness on the electrode material to form a second dielectric protective layer to obtain a primary ceramic dielectric filter. By alternately printing the electrode material and the dielectric slurry, the combination of the dielectric and the electrode can be ensured, the density of the ceramic filter can be improved, and the conductivity of the ceramic filter can be improved; the primary ceramic filter is dried and laminated to obtain a finished ceramic filter. By drying and laminating the primary ceramic filter, sintering shrinkage can be prevented, ensuring that the ceramic filter has good electrical properties and mechanical strength, and improving the pressure resistance of the ceramic filter. It can meet specific frequency selection and signal processing requirements, and can be used as a high-capacity, high-voltage, and high-current filter product, which increases the application range of the ceramic filter.

[0060] In some embodiments of the present application, the ceramic powder is a mixed material of barium titanate, strontium titanate, and zirconium titanium. Those skilled in the art can select the material of the ceramic powder according to actual conditions. The embodiments of the present application do not limit the material of the ceramic powder.

[0061] Reference Figure 2 As shown, Figure 2 is a flow chart of another method for preparing a ceramic filter provided in an embodiment of the present application. The method for preparing a ceramic filter includes but is not limited to steps S610 to S630. Specifically,

[0062] Step S610: cutting and debonding the ceramic dielectric filter that has been dried and laminated;

[0063] Step S620: performing sintering, end-sealing and end-burning treatments on the ceramic dielectric filter that has undergone drying and lamination treatments;

[0064] Step S630: electroplating the dried and laminated ceramic filter to obtain a finished ceramic filter.

[0065] In some embodiments of the present application, after the primary ceramic filter is dried and laminated, the preparation method of the ceramic filter further includes cutting and debinding the ceramic filter that has been dried and laminated. By cutting the ceramic filter to form the desired shape and size, the debinding of the ceramic filter can remove any organic matter that may remain during the production process, such as adhesives or lubricants; the debinding process is usually carried out in a high-temperature furnace to ensure that all residues are thoroughly removed. Afterwards, the ceramic filter is sintered, capped and burned. The ceramic filter is sintered to promote the densification and strengthening of the electrode material and the dielectric slurry, thereby improving the physical and electrical properties of the ceramic filter; the ceramic filter is capped to add a protective layer to the end of the ceramic filter to prevent the intrusion of moisture and pollutants, which usually involves coating a layer of glass or other protective materials; after the ceramic filter is capped, the ceramic filter is burned to solidify the capping material at the end of the ceramic filter. Finally, the ceramic filter is electroplated, for example, a layer of conductive material, such as gold or silver, is added to the surface of the ceramic filter to improve its conductivity and reliability. The electroplating process can increase the durability and corrosion resistance of the filter. By performing the above steps on the ceramic filter that has been dried and laminated, the final ceramic filter product should have good electrical properties and mechanical strength, and can meet specific frequency selection and signal processing requirements.

[0066] Reference Figure 3 , Figure 3 1 is a flow chart of a method for pretreating a primary slurry to obtain a dielectric slurry provided in an embodiment of the present application. The method for pretreating a primary slurry to obtain a dielectric slurry includes but is not limited to steps S210 to S220. Specifically,

[0067] Step S210: adding a solvent, a plasticizer, and a dispersant to the primary slurry, stirring and mixing, to obtain a mixed solvent;

[0068] Step S220: placing the mixed solvent on an emulsifier for emulsification, or placing the mixed solvent on a roller mill for a preset number of times to obtain a medium slurry.

[0069] In some embodiments of the present application, the preparation method of the ceramic filter includes: first, taking the adhesive and the ceramic powder, mixing and stirring to obtain a primary slurry, and then pre-treating the primary slurry to obtain a dielectric slurry. Specifically, adding a solvent, a plasticizer, and a dispersant to the primary slurry for stirring and mixing to obtain a mixed solvent. It can be understood that the solvent is used to help mix and dissolve additives such as plasticizers and dispersants, and to help form a uniform slurry. The plasticizer is used to increase the fluidity and flexibility of the slurry to make it easier to form. The dispersant is used to ensure that the ceramic powder is evenly dispersed in the slurry to avoid agglomeration. By stirring and mixing the above solvents, it is ensured that all ingredients are evenly mixed to form a stable mixed solvent. The mixed solvent is placed on an emulsifier for emulsification to obtain a dielectric slurry, or the mixed solvent is placed on a roller mill for a preset number of times to further mix and refine the slurry to make it more uniform and delicate, and obtain a dielectric slurry. After emulsification or rolling, the obtained dielectric slurry has good uniformity and fluidity, and is suitable for subsequent molding processes.

[0070] Reference Figure 4 , Figure 4 1 is a flow chart of a method for placing a mixed solvent on a roller mill for a preset number of times to obtain a dielectric slurry provided by an embodiment of the present application. The method for placing a mixed solvent on a roller mill for a preset number of times to obtain a dielectric slurry includes but is not limited to steps S221 to S222. Specifically,

[0071] Step S221: heating the mixed solvent to raise the temperature of the mixed solvent to 60° C.;

[0072] Step S222: stirring the mixed solvent at a speed of 60 rpm for 20 minutes, and rolling on a roller mill for 1 to 10 times to make the viscosity of the mixed solvent below 40 KCP, to obtain a medium slurry.

[0073] In some embodiments of the present application, the method of placing a mixed solvent on a roller mill and rolling it for a preset number of times to obtain a dielectric slurry includes: first, heating the mixed solvent to raise the temperature of the mixed solvent to 60°C. Heating can help the mixed solvent to dissolve and mix better and improve the efficiency of stirring and dispersion. After that, stirring at a speed of 60 rpm in the heated mixed solvent for 20 minutes. Stirring helps to evenly distribute the dispersant and plasticizer, as well as fully disperse the ceramic powder; rolling the stirred mixed solvent on a roller mill 1 to 10 times. Rolling is a physical treatment method that can further refine the slurry, reduce its viscosity, and improve its uniformity. Through rolling treatment, the viscosity of the mixed solvent is adjusted to below 40KCP. Viscosity is an important indicator of slurry fluidity and is crucial to ensuring the molding quality of ceramic dielectric filters.

[0074] In some embodiments of the present application, after obtaining the dielectric slurry in step S220, the method for preparing the ceramic dielectric filter further includes step S230, specifically:

[0075] Step S230: selecting medium slurry, and performing viscosity detection, solid content detection, fineness detection, and vacuum defoaming treatment on the medium slurry to ensure that the medium slurry meets the required medium slurry particle size requirements.

[0076] In the process of preparing the ceramic filter, after drying and laminating, the next steps include a series of tests and treatments on the dielectric slurry to ensure that its performance meets the requirements, including: viscosity test of the dielectric slurry to ensure that the viscosity of the dielectric slurry is between 1000Pa.S and 40000Pa.S. This range of viscosity is suitable for subsequent molding; test the solid content of the dielectric slurry to evaluate the proportion of solid matter in the slurry. The solid content is crucial to the performance and stability of the dielectric slurry. It is necessary to ensure that the solid content is 35% to 70%. Fineness test is performed to ensure the uniformity and fineness of the slurry particles. Fineness test of the dielectric slurry. The fineness directly affects the performance of the dielectric after sintering. It is necessary to ensure that the fineness of the dielectric slurry is 0.2μm to 5μm. The vacuum method is used to remove bubbles in the dielectric slurry to improve the density and uniformity of the dielectric slurry and prevent defects in subsequent processing. Through viscosity testing, solid content testing, fineness testing, vacuum defoaming treatment and other treatments, the dielectric slurry will reach the required particle size and performance requirements, laying the foundation for subsequent molding and sintering processes. These steps ensure that the final ceramic dielectric filter has good electrical properties and mechanical strength.

[0077] Reference Figure 5 As shown, Figure 5 is a flow chart of a method for preparing an adhesive provided in an embodiment of the present application. The method for preparing the adhesive includes but is not limited to steps S700 to S710. Specifically,

[0078] Step S700: selecting polyvinyl butyral, cellulose resin and acrylic resin as raw materials for preparing an adhesive;

[0079] Step S710: polyvinyl butyral, cellulose resin and acrylic resin are mixed in a ratio of 6:2:1, added into an organic solvent and the organic solvent is heated to 30° C. to 80° C. so that the raw materials of the adhesive account for 45%-75% of the organic solvent, thereby obtaining an adhesive.

[0080] In some embodiments of the present application, the preparation method of the adhesive includes: selecting polyvinyl butyral, cellulose resin and acrylic resin as raw materials for preparing the adhesive, then selecting 6 parts of polyvinyl butyral, 2 parts of cellulose resin and 1 part of acrylic resin for mixing, and adding the mixed raw materials of the adhesive to an organic solvent and heating the organic solvent to 30°C to 80°C. Heating helps to increase the dissolution rate and uniformity of polyvinyl butyral, cellulose resin and acrylic resin in the organic solvent. By adjusting the ratio of polyvinyl butyral, cellulose resin and acrylic resin to the organic solvent, the raw materials of the adhesive account for 45%-75% of the organic solvent. This ratio range can ensure the viscosity and bonding performance of the adhesive.

[0081] In some embodiments of the present application, the organic solvent includes an alcohol solvent and an ester solvent. Those skilled in the art may select a suitable organic solvent according to actual conditions. The embodiments of the present application do not limit the type of organic solvent.

[0082] In some embodiments of the present application, polyvinyl butyral, cellulose resin, and acrylic resin are mixed in a ratio of 6:2:1, or polyvinyl butyral, cellulose resin, and acrylic resin are mixed in a ratio of 6:3:1. The mixing ratio of polyvinyl butyral, cellulose resin, and acrylic resin can be set according to the viscosity of the adhesive required in actual conditions. The embodiments of the present application do not limit the mixing ratio of polyvinyl butyral, cellulose resin, and acrylic resin.

[0083] In one embodiment of the present application, polyvinyl butyral, cellulose resin, and acrylic resin are mixed in a ratio of 6:3:1. 12 g of polyvinyl butyral, 6 g of cellulose resin, and 2 g of acrylic resin are mixed and added to a mixed organic solvent of 45 g of alcohol solvent and 35 g of ester solvent. The organic solvent is heated to 30°C to 80°C so that the raw materials of the adhesive account for 45%-75% of the organic solvent to obtain an adhesive.

[0084] In some embodiments of the present application, a polyester film is pasted on a metal carrier plate, and a dielectric slurry of a preset thickness is printed on the polyester film to obtain a first dielectric protective layer, including: printing the polyester film on the metal carrier plate by a stacking static pressing process, and pasting a layer of 0.2mm thick and smooth polyester film on a 216mm*216mm*0.8mm metal carrier plate, and the film must be pasted flat. After that, the dielectric slurry is printed layer by layer on the polyester film until the thickness of the dielectric slurry reaches a preset thickness, which is 2μm-200μm. Those skilled in the art can set the preset thickness of the dielectric slurry according to actual conditions. Since the printing slurry has high viscosity and high solid content, less organic solvent is added, and less solvent volatilization occurs, which has energy-saving and environmental protection effects. Each layer of dielectric slurry is dried at 40°C to 70°C for 5 to 25 minutes. Alternatively, the dielectric diaphragm is printed on the polyester film by a stacking static pressing process, which can save the number of printing layers and improve production efficiency.

[0085] Reference Figure 6 As shown, Figure 6 is a flow chart of a method for obtaining an electrode material provided in an embodiment of the present application. The method for obtaining an electrode material includes but is not limited to steps S410 to S430. Specifically,

[0086] Step S410: printing a first layer of electrode slurry with a thickness of 1 μm to 15 μm on the first dielectric protection layer, and placing it in a temperature environment of 30° C. to 80° C. to dry for 5 minutes to 25 minutes;

[0087] Step S420: printing a second dielectric protection layer on the dried first dielectric protection layer, and performing a drying process, printing a second layer of electrode paste with a thickness of 2 μm to 200 μm on the second dielectric protection layer in an organic solvent including an alcohol solvent and an ester solvent, and placing the second layer in an environment of 30° C. to 80° C. to dry for 10 minutes to 50 minutes;

[0088] Step S430: alternately printing a dielectric protection layer and an electrode slurry on the dried electrode slurry until the thickness of the electrode slurry of the organic solvent including an alcohol solvent and an ester solvent reaches a preset thickness, and drying is performed after each printed dielectric protection layer or electrode slurry to obtain an electrode material.

[0089] In some embodiments of the present application, the preparation method of the electrode material includes: printing a first layer of electrode slurry with a thickness of 1 μm to 15 μm on the first dielectric protective layer, and then drying it; printing a second dielectric protective layer on the dried first dielectric protective layer and drying it, and then printing an electrode slurry with a thickness of 2 μm to 200 μm on the second dielectric protective layer and drying it; then, the dielectric protective layer and the electrode slurry until the thickness of the electrode slurry reaches a preset thickness, repeating the above steps, alternately printing the dielectric protective layer and the electrode slurry until the electrode slurry reaches a preset thickness, and drying each time a dielectric protective layer or a layer of electrode slurry is printed, ensuring the stability and performance of the electrode material, so as to ensure good adhesion between layers and the performance of the material, and obtain the electrode material. When preparing the electrode material, it is crucial to accurately control the thickness and drying time of each layer to ensure that the performance of the final product meets the design requirements.

[0090] Reference Figure 7 As shown, Figure 7 1 is a flowchart of a method for drying and laminating a primary ceramic filter to obtain a finished ceramic filter provided by an embodiment of the present application. The method for drying and laminating a primary ceramic filter to obtain a finished ceramic filter includes but is not limited to steps S601 to S602. Specifically,

[0091] Step S601: placing the primary ceramic filter in a temperature environment of 30° C. to 50° C. for drying for 1 to 24 hours;

[0092] Step S602: Laminating the dried primary ceramic filter under an air pressure of 20 MPa to 100 MPa for 5 to 60 minutes.

[0093] In some embodiments of the present application, a method for drying and laminating a primary ceramic filter to obtain a finished ceramic filter includes: placing the primary ceramic filter in a temperature environment of 30°C to 50°C for drying, which can remove moisture and solvent in the primary ceramic filter to facilitate subsequent lamination. The drying time is usually controlled to be 1 to 24 hours, and the specific time depends on the size of the ceramic filter, the formula of the slurry, and the required degree of drying. The dried ceramic filter needs to be laminated for further compaction and curing. The lamination process is carried out at a certain pressure and temperature to ensure the density and uniformity of the material. The air pressure conditions during the lamination process are usually controlled between 20MPa and 100MPa. This pressure range helps to discharge bubbles that may be generated during the lamination process and ensure good bonding between materials. The lamination time is determined according to the required degree of curing and material properties, generally between 5 minutes and 60 minutes. A longer lamination time helps to improve the mechanical strength and electrical properties of the filter. By precisely controlling the conditions of drying and lamination, the quality and performance of the ceramic filter can be effectively improved to ensure its reliability and stability in high-frequency applications.

[0094] The embodiments of the present invention are described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing a ceramic dielectric filter, characterized in that: include: The binder and the ceramic powder are mixed and stirred to obtain a primary slurry; Pre-treating the primary slurry to obtain a medium slurry; A polyester film is attached to the metal carrier plate, and the dielectric slurry having a preset thickness is printed on the polyester film to obtain a first dielectric protective layer; Printing an electrode slurry with a preset thickness on the first dielectric protection layer, and performing a drying process to obtain an electrode material; Printing the dielectric slurry with a preset thickness on the electrode material to form a second dielectric protection layer to obtain a primary ceramic dielectric filter; The primary ceramic filter is dried and laminated to obtain a finished ceramic filter.

2. The method for preparing a ceramic dielectric filter according to claim 1, characterized in that: After the primary ceramic filter is dried and laminated, the method further comprises: Carry out cutting and debonding treatment on the ceramic dielectric filter which has been dried and laminated; The ceramic dielectric filter that has undergone drying and lamination treatment is subjected to sintering treatment, end-sealing treatment and end-burning treatment; The dried and laminated ceramic filter is electroplated to obtain a finished ceramic filter.

3. The method for preparing a ceramic dielectric filter according to claim 1, characterized in that: The pre-treating of the primary slurry to obtain the medium slurry comprises: Adding a solvent, a plasticizer, and a dispersant to the primary slurry, stirring and mixing, to obtain a mixed solvent; The mixed solvent is placed on an emulsifier for emulsification, or the mixed solvent is placed on a roller mill for a preset number of times to obtain a medium slurry.

4. The method for preparing a ceramic dielectric filter according to claim 3, characterized in that: Placing the mixed solvent on a roller mill and rolling it for a preset number of times to obtain a medium slurry comprises: The mixed solvent is heated to 60° C. The mixed solvent was stirred at a speed of 60 rpm for 20 minutes, and rolled on a roller mill for 1 to 10 times to make the viscosity of the mixed solvent below 40 KCP, thereby obtaining a medium slurry.

5. The method for preparing a ceramic dielectric filter according to claim 3, characterized in that: After obtaining the medium slurry, the method further comprises: The medium slurry is selected, and the medium slurry is subjected to viscosity test, solid content test, fineness test, and vacuum defoaming treatment to ensure that the medium slurry meets the required medium slurry particle size requirement.

6. The method for preparing a ceramic dielectric filter according to claim 1, characterized in that: The preparation method of the adhesive comprises: Polyvinyl butyral, cellulose resin and acrylic resin are selected as raw materials for preparing the adhesive; The polyvinyl butyral, cellulose resin and acrylic resin are mixed in a ratio of 6:2:1, added into an organic solvent and the organic solvent is heated to 30° C. to 80° C. so that the raw materials of the adhesive account for 45%-75% of the organic solvent to obtain an adhesive.

7. The method for preparing a ceramic dielectric filter according to claim 1, characterized in that: The step of printing an electrode slurry of a preset thickness on the first dielectric protective layer and performing a drying process to obtain an electrode material comprises: Printing a first layer of electrode slurry with a thickness of 1 μm to 15 μm on the dielectric protection layer, and placing it in a temperature environment of 30° C. to 80° C. to dry for 5 minutes to 25 minutes; Printing a second layer of electrode slurry with a thickness of 2 μm to 200 μm on the dried dielectric protective layer, and placing it in an environment of 30° C. to 80° C. to dry for 10 minutes to 50 minutes; The dielectric protection layer and the electrode paste are alternately printed on the dried second electrode paste layer until the thickness of the electrode paste reaches a preset thickness, and each printed dielectric protection layer or electrode paste layer is dried to obtain an electrode material.

8. The method for preparing a ceramic dielectric filter according to claim 1, characterized in that: The step of drying and laminating the primary ceramic filter to obtain a finished ceramic filter comprises: The primary ceramic filter is placed in a temperature environment of 30° C. to 50° C. for drying for 1 to 24 hours; The dried primary ceramic filter is placed under an air pressure of 20 MPa to 100 MPa for lamination for 5 to 60 minutes.

9. The method for preparing a ceramic dielectric filter according to claim 4, characterized in that: The organic solvent includes alcohol solvent and ester solvent.

10. The method for preparing a ceramic dielectric filter according to claim 1, characterized in that: The ceramic powder is a mixed material of barium titanate series, strontium titanate series and zirconium titanium series.

Citation Information

Patent Citations

  • Porous plate type array structure ceramic capacitor filter preparation method

    CN101145446A

  • Application of printing and overlapping membrane method in preparation of multiaperture-type array ceramic filters

    CN101667676A

  • Method for preparing ceramic dielectric filter

    CN109534789A

  • Production of ceramic slurry, ceramic green sheet and laminated ceramic electronic parts

    JP2001039773A

  • Dielectric filter, antenna duplexer

    KR1020020095211A